Determination of copper and other trace elements in serum samples from patients with biliary tract cancers - Reberšek, Martina (Radiology and oncology (Ljubljana), 2024)
Background Biliary tract cancers (BTCs) are usually diagnosed at an advanced stage, when the disease is incurable. Currently used tumor biomarkers have limited diagnostic value for BTCs, so there is an urgent need for sensitive and specific biomarkers for their earlier diagnosis. Deregulation of the homeostasis of trace elements is involved in the carcinogenesis of different cancers, including BTCs. The objective of the study is to determine/compare the total concentrations of copper (Cu), zinc (Zn) and iron (Fe) and the proportions of free Cu and Cu bound to ceruloplasmin (Cp) and the isotopic ratio of 65Cu/63Cu in serum samples from healthy volunteers and cancer patients using inductively coupled plasma-mass spectrometry-based methods (ICP-MS).
Keywords: baker; biliarni trakt; biološki označevalci; elementi v sledovih; onkologija; rak žolčnika